A case study assessing possession regain patterns in English Premier League Football. (2nd November 2019) - Jamil, Mikael
ABSTRACT: Recent years have seen significant attention awarded to possession regains in football. This case study examines possession regain patterns of an elite English Premier League team across three seasons from the 2015–16 season to the 2017–18 season (n = 106). A series of regressions are conducted in order to determine: what impact possession regains had on attacking performance, which players were most productive with possession post regains and which other factors influenced the number of successful possession regains by the subject team. Results revealed that possession regains in the opponent's half were highly significant and had a positive impact upon attacking performance (p = 0.006). Possession regains that occurred on the left-hand side of the playing field led to more productivity in front of goal (p = 0.028). The quality of the opponent was also revealed to have a significant impact upon the number of possession regains (p = 0.025). It is concluded that possession regains high up the playing field are crucial to the subject team's attacking success. Furthermore, players performing on the left side of the playing field were more productive with possession regains than those playing centrally or on the right.